2016
DOI: 10.1111/cogs.12469
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Attributions and Behavioral Predictions

Abstract: Recent work has shown that knowledge attributions affect how people think others should behave, more so than belief attributions do. This paper reports two experiments providing evidence that (a) knowledge attributions also affect behavioral predictions more strongly than belief attributions do, and (b) knowledge attributions facilitate faster behavioral predictions than belief attributions do. Thus, knowledge attributions play multiple critical roles in social cognition, guiding judgments about how people sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
(26 reference statements)
1
8
0
1
Order By: Relevance
“…Knowledge attributions consistently predicted behavioral predictions more strongly than belief attributions did. Moreover, a causal search algorithm suggested that knowledge attributions caused behavioral predictions in contexts where belief attributions did not (Turri, 2016a). Whereas previous research has demonstrated a unique role for knowledge attributions in evaluating how people should behave (e.g., Turri, 2015a, 2015b; Turri, Friedman, & Keefner, 2017), these findings suggest a previously unrecognized role for knowledge attributions in predicting how people will behave.…”
Section: Do Attributions Of Knowledge Depend On Belief?mentioning
confidence: 99%
“…Knowledge attributions consistently predicted behavioral predictions more strongly than belief attributions did. Moreover, a causal search algorithm suggested that knowledge attributions caused behavioral predictions in contexts where belief attributions did not (Turri, 2016a). Whereas previous research has demonstrated a unique role for knowledge attributions in evaluating how people should behave (e.g., Turri, 2015a, 2015b; Turri, Friedman, & Keefner, 2017), these findings suggest a previously unrecognized role for knowledge attributions in predicting how people will behave.…”
Section: Do Attributions Of Knowledge Depend On Belief?mentioning
confidence: 99%
“…Cada criterio conceptual, con respecto al método, no solo responde a tendencias y teorías según el contexto de convergencia de los autores, algunos con discrepancias visibles, otros con ejemplificaciones sobre resultados, lo importante, es el aporte de establecer criterios de evaluación científica sobre resultados obtenidos, por lo que, según la finalidad, el entorno circundante del fenómeno en sí mismo será el método a emplear por el investigador, donde explicar la conexión entre el conocimiento y la verdad es una necesidad (Turri, 2017;Blouw et al, 2017).…”
Section: Método Trascendentalunclassified
“…Relatedly, Turri () argues that knowledge attributions play a different functional role in mindreading than belief (or, in Nagel's terms, nonfactive) attributions. Knowledge attributions lead to faster and more reliable behavioral predictions than belief attributions.…”
Section: Mindreading Broadly Construedmentioning
confidence: 99%